PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA DAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Nyolan Lestari; Deddy Marciano; Arif Herlambang (Perpustakaan Universitas Surabaya, 2018)
This study aims to analyze the effect of good corporate governance (GCG) towards firm performance using tobin’s q ratio (TOBIN_Q) and dividend policy using dividend payout ratio (DPR) as a proxy in manufature sector companies listed in Indonesia Stock Exchange (BEI) in the period 2012-2016.This research uses quantitative approach with multiple linear regression analysis model. This study uses sample of firms which are listed on manufature sector in IDX on 2012 – 2016. The number of final samples used in this study were 112 business entities with 560 observations.